PENGEMBANGAN USAHA HOME INDUSTRI (Studi Kasus Usaha Kerupuk Sagu Di Desa Pulau Kijang Kecamatan Kuantan Hilir Kabupaten Kuantan Singingi) - Fitri Mila Sari; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at Desa Kijang Kecamatan Kuantan Hilir Kuantan Singingi Regency. The purpose of this research is to know the background of establishing Home Business of Sago Cracker Industry. The focus of this research is about the economic condition of Home Industry entrepreneurs Sago Crackers. The technique of determining the sample by purposive sampling and set the number of samples as many as 9 people. The author uses qualitative descriptive method and Instrument data is observation, interview and documentation. The research conducted found that the Home Profile of Sago cracker industry in Desa Kijang consists of the following characteristics: Business capital, The study found that the average business capital issued is Rp 1,700,000-2,500,000. Labor, Research finds that the average research subject employs surrounding communities and members of their families to help develop the Home Industry of sago crackers in the village of Kijang Island. The marketing system, Research finds that the average research subjects do marketing the product by way of sago crackers in stalls, supermarkets, open booths, and sell through social media. The socioeconomic conditions of the community after the Home Industry of sago crackers in Desa Kijang are as follows: Education, Research found that the average of research subjects before the Home Industry of sago crackers in Desa Kijang Island was pessimistic with education and surrendered with the education of their children. The research found that the average of research subjects before the Home Industry of sago crackers in Desa Kijang Island only had one permanent job, after the Home Industry of Sago crackers the subject of research also remained with the old work but more focus on Home Industry of sago chips that run . Income, All subjects experiencing income changes after the Home Industry sago crackers. Keywords: Home Industry, Rational Choice, Social Networking